Three-year follow-up from a phase 3 study of SB3 (a trastuzumab biosimilar) versus reference trastuzumab in the neoadjuvant setting for human epidermal growth factor receptor 2–positive breast cancer. (October 2019) - Pivot, Xavier; Pegram, Mark; Cortes, Javier; Lüftner, Diana; Lyman, Gary H.; Curigliano, Giuseppe; Bondarenko, Igor; Yoon, Ye Chan; Kim, Younsoo; Kim, Chul
Abstract: Background: We assessed long-term cardiac safety and efficacy in patients with human epidermal growth factor receptor 2–positive early breast cancer treated with a trastuzumab biosimilar (SB3) or its reference product, trastuzumab (TRZ), in a phase 3 study. Methods: Patients who completed the phase 3 study could be enrolled in this extension study. The outcomes included the incidence of symptomatic congestive heart failure (CHF), asymptomatic significant left ventricular ejection fraction (LVEF) decrease, incidence of other cardiac events, event-free survival (EFS), and overall survival. In post hoc analysis, the Cox proportional hazards regression model was used to assess factors associated with EFS. Results: A total of 367 patients were enrolled in the study (SB3, n = 186; TRZ, n = 181). The median follow-up duration from the main study enrolment was 40.8 and 40.5 months for SB3 and TRZ, respectively. During the two-year follow-up after adjuvant therapy, incidence of asymptomatic significant LVEF decrease was rare (SB3, n = 1; TRZ, n = 2), with all patients recovering with LVEF ≥ 50%, and no cases of symptomatic CHF or other cardiac events were reported. At 3 years, the EFS was 91.9% with SB3 and 85.2% with TRZ. The number of patients with events was 17 (9.1%) with SB3 and 31 (17.1%) with TRZ [hazard ratio: 0.47, 95% confidence interval: 0.26–0.87]. Antibody-dependent cell-mediated cytotoxicity (ADCC) activity and the breast pathologic complete response rate were the factors associated with EFS. Conclusion: Cardiotoxicity was rare in this extension study. EFS was higher with SB3 versus TRZ, with post hoc analysis suggesting that a downward drift in ADCC activity was a contributing factor. Clinical trial registration numbers: NCT02771795 (EudraCT 2015-005663-17). Highlights: Cardiotoxicity was rare and similar between SB3 (a trastuzumab biosimilar) and Herceptin® (trastuzumab [TRZ]) up to 3 years. Three-year event-free survival (EFS) was significantly higher in SB3 compared with TRZ. In some TRZ lots, a downward drift in antibody-dependent cell-mediated cytotoxicity–related quality attributes was observed. Post hoc analyses suggest a downward drift in TRZ could have affected EFS difference. Three-year EFS and overall survival were comparable between SB3 and non-drifted TRZ.